Implementation of Debt Restructuring in Indonesia during the Enactment of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations - Astuti, Eliska Desi; Suraji, Suraji (MultiTech Publisher, 2024)
This research aims to determine and analyze the implementation of debt restructuring in Indonesia during the enactment of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The research method in this writing is normative legal research using a statutory approach, case approach, historical approach, comparative approach and conceptual approach. The types of legal materials in this research are primary legal materials and secondary legal materials. The technique for collecting legal materials is carried out by conducting literature studies. Then the legal material analysis technique is deductive using the deduction method. The results of the research in this paper are that the implementation of Law No. 37 of 2004 concerning Bankruptcy and Postponement of Payment Obligations is currently felt to not provide sufficient protection to debtors with good intentions.